1992
DOI: 10.1111/j.1751-1097.1992.tb02184.x
|View full text |Cite
|
Sign up to set email alerts
|

INACTIVATION OF LAMBDA PHAGE WITH 658 nm LIGHT USING A DNA BINDING PORPHYRIN SENSITIZER

Abstract: Exposure of lambda phage to 658 nm light in the presence of 5,10,15,20-tetrakis-(1-methyl-4-pyridyl)-21H,23H-porphine, tetra-p-tosylate leads to complete (greater than 7 logs) inactivation as measured by the plaque assay. The sensitizer without light and 658 nm photolysis of lambda phage in the absence of sensitizer do not lead to a measurable decrease in viral inactivity. Viral inactivation is not dependent upon the presence of oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 8 publications
1
27
0
1
Order By: Relevance
“…Tetra- and tricationic porphyrin derivatives ( meso -tetrakis(1-methylpyridinium-4-yl)porphyrin and 5-(pentafluorophenyl)-10,15,20-tris(1-methylpyridinium-4-yl)porphyrin, respectively) lead to complete T4-like phage inactivation (~7 log) after 270 min of irradiation with 40 W m −2 [66]. This tetracationic porphyrin showed similar results in another study (7 log of reduction) for lambda phage inactivation, when irradiated with light of 658 nm [58]. Increasing porphyrin concentration at a fixed light dose leads to increased viral inactivation [58].…”
Section: Factors Affecting Viral Pdimentioning
confidence: 61%
See 2 more Smart Citations
“…Tetra- and tricationic porphyrin derivatives ( meso -tetrakis(1-methylpyridinium-4-yl)porphyrin and 5-(pentafluorophenyl)-10,15,20-tris(1-methylpyridinium-4-yl)porphyrin, respectively) lead to complete T4-like phage inactivation (~7 log) after 270 min of irradiation with 40 W m −2 [66]. This tetracationic porphyrin showed similar results in another study (7 log of reduction) for lambda phage inactivation, when irradiated with light of 658 nm [58]. Increasing porphyrin concentration at a fixed light dose leads to increased viral inactivation [58].…”
Section: Factors Affecting Viral Pdimentioning
confidence: 61%
“…The damages caused by photodynamic reactions on unsaturated lipids present in their envelopes and/or on major envelope proteins, which act as PS binding-sites, modify their structure and avoid cell infection and virus replication [50,84]. However, some studies showed that non-enveloped viruses can also be efficiently inactivated by the toxic action of PS [55,56,58,62,64,65,66,67,73,81,87,88,94,122]. …”
Section: Molecular Targets Of Antiviral Pdimentioning
confidence: 99%
See 1 more Smart Citation
“…Using electron microscopy, a massive destruction of virus envelopes was detected after treatment with phthalocyanines containing metal ligands, leading to a significant decrease of virus infectivity of several enveloped viruses [Varicella zoster virus (VZV), HSV-1 and HSV-2], whereas non-enveloped adenovirus was largely resistant to the treatment (Smetana et al 1994). Nevertheless, several studies have presented evidence that non-enveloped viruses are also sensitive to direct PACT inactivation (Kasturi and Platz 1992;Gaspard et al 1995;Costa et al 2008Costa et al , 2010Zupan et al 2008), which might be explained by photoactivated protein crosslinking that leads to direct damage or loss of proteins, and finally the loss of infectivity (Lenard et al 1993;Smetana et al 1997;Orosz et al 2013). At physiological conditions, non-enveloped viruses have negatively charged capsids and enveloped viruses harbour negatively charged glycoproteins on their surface, and are thus likely directly targeted by cationic porphyrins via electrostatic interactions, like previously described for Gram(−) bacteria (Karlin and Brendel 1988;Michen and Graule 2010;Liu et al 2015).…”
Section: Molecular Targets Of Antiviral Pactmentioning
confidence: 99%
“…Ââàжàþòü, ùî â³ðóñè, ÿê³ ìàþòü ñóïåðêàïñèä ìîжóòü áóòè ³íàêòèâîâàí³ âíàñë³äîê ïîøêîäжåíü, ñïðè÷èíåíèõ фîòîäèíàì³÷íèìè ðåàêö³ÿìè â ¿õ ïðîòå¿íîâèõ ìîëåêóëàõ [5]. Ùîäî â³ðóñ³â, ÿê³ íå ìàþòü ñóïåðêàïñèäó, º ïðèïóùåííÿ, ùî ¿õ ³íàêòèâàö³ÿ â ïðèñóòíîñò³ ïîðф³ðèí³â îáóìîâëåíà âçàºìî䳺þ îñòàíí³õ ç íóêëå¿íîâèìè êèñëîòàìè [6,8].  îñòàíí³é ÷àñ ïðè âèâ÷åíí³ àíòèâ³ðóñíèõ âëàñòèâîñòåé ³ ìåõàí³çì³â 䳿 íîâèõ ñïîëóê øèðîêî âèêîðèñòîâóþòü áàêòåð³îфàгè, ÿê³ ñëóгóþòü ìîäåëëþ ïàòîгåííèõ ÄНÊ â³ðóñ³â ëþäèíè [1,4].…”
unclassified